Women commencing anastrozole, letrozole or tamoxifen for early breast cancer: The impact of comorbidity and demographics on initial choice - Kemp, A.; Preen, D.; Saunders, C.; Boyle, F.; Bulsara, M.; Holman, C.; Malacova, Eva; Roughead, E. (Public Library of Science, 2014)
Background: Australian clinical guidelines recommend endocrine therapy for all women with hormone-dependent early breast cancer. Guidelines specify tamoxifen as first-line therapy for pre-menopausal women, and tamoxifen or an aromatase inhibitor (AI) for post-menopausal women depending on the risk of recurrence based on tumour characteristics including size. Therapies have different side effect profiles; therefore comorbidity may also influence choice. We examined comorbidity, and the clinical and demographic characteristics of women commencing different therapies. Patients and Methods: We identified the first dispensing of tamoxifen, anastrozole or letrozole for women diagnosed with invasive breast cancer in the 45 and Up Study from 2004-2009 (N = 1266). Unit-level pharmacy and medical service claims, hospital, Cancer Registry, and self-reported data were linked to determine menopause status at diagnosis, tumour size, age, comorbidities, and change in subsidy restrictions. Chi-square tests and generalised regression models were used to compare the characteristics of women commencing different therapies. Results: Most pre-menopausal women commenced therapy with tamoxifen (91%). Anastrozole was the predominant therapy for post-menopausal women (57%), followed by tamoxifen (28%). Women with osteoporosis were less likely to commence anastrozole compared with tamoxifen (anastrozole RR = 0.7, 95% CI = 0.5-0.9). Women with arthritis were 1.6- times more likely to commence letrozole than anastrozole (95% CI = 1.1-2.1). Tamoxifen was more often initiated in women with tumours > 1 cm, who were also =75 years. Subsidy restriction changes were associated with substantial increases in the proportion of women commencing AIs (anastrozole RR = 4.3, letrozole RR = 8.3). Conclusions: The findings indicate interplay of comorbidity and therapy choice for women with invasive breast cancer. Most post-menopausal women commenced therapy with anastrozole; however, letrozole and tamoxifen were more often initiated for women with comorbid arthritis and osteoporosis, respectively. Tamoxifen was also more common for women with tumours > 1 cm and aged =75 years. Subsidy restrictions appear to have strongly influenced therapy choice. © 2014 Kemp et al.